Malaysia's wasted decade, 2004-2014 - M. Bakri Musa (Zi Publications Sdn Bhd, 2016)
These essays chronicle the continued erosion of Malaysia's once reliable institutions, the corrosion of its economy through endemic corruption and crony capitalism, and the polarization of its citizens along race, region and religion. These are the crippling consequences of the toxic leadership of the triad of the vacuous Abdullah Badawi, rudderless Najib Razak, and the sclerotic ruling party, UMNO. Not an auspicious beginning as Malaysia enters the new millennium.